2019
DOI: 10.1111/jcpp.13045
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental influences on the stability of psychotic experiences and negative symptoms in adolescence

Abstract: Background Psychotic experiences (PEs) such as paranoia and hallucinations, and negative symptoms (NS) such as anhedonia and flat affect are common in adolescence. Psychotic experiences and negative symptoms (PENS) increase risk for later psychiatric outcomes, particularly when they persist. The extent to which genetic and environmental influences contribute to the stability of PENS in mid‐to‐late adolescence is unknown. Methods Using the Specific Psychotic Experiences Questionnaire (SPEQ) twice across ~9 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“… 14 Persistent psychotic experiences may therefore reflect an underlying neurodevelopmental vulnerability, which is phenotypically expressed through neurocognitive impairments, decreased social skills and increased psychopathological risk, as shown in the current study. Evidence from twin studies has indicated a genetic component in the stability of psychotic experiences over time, 31 and it has been reported that cumulative exposure to environmental risk factors (such as trauma, cannabis use and urbanicity) affect the likelihood that psychotic experiences become persistent. 28 …”
Section: Discussionmentioning
confidence: 99%
“… 14 Persistent psychotic experiences may therefore reflect an underlying neurodevelopmental vulnerability, which is phenotypically expressed through neurocognitive impairments, decreased social skills and increased psychopathological risk, as shown in the current study. Evidence from twin studies has indicated a genetic component in the stability of psychotic experiences over time, 31 and it has been reported that cumulative exposure to environmental risk factors (such as trauma, cannabis use and urbanicity) affect the likelihood that psychotic experiences become persistent. 28 …”
Section: Discussionmentioning
confidence: 99%
“…In terms of genetic factors, several studies have investigated their influence on PENS at single time-points or assessments (Ronald & Pain, 2018 ), and findings from a small number of family studies further suggest that genetic factors are associated with the development of PENS (Ericson, Tuvblad, Raine, Young-Wolff, & Baker, 2011 ; Havers, Taylor, & Ronald, 2019 ; Janssens et al, 2016 ; Wigman et al, 2011a ). The prior study with the largest sample size ( N = 1448 twin pairs) found that 38–62% of the covariance in separate PENS dimensions measured across two time-points in adolescence was accounted for by genetic influences (Havers et al, 2019 ). Genome-wide polygenic scores (GPS) can also be used as an index of an individual's polygenic propensity to a given outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Havers, Taylor, and Ronald () tracked psychotic experiences and negative symptoms over a 9‐month longitudinal observation in 1,448 adolescent twin pairs. There was considerable stability of the phenotype over this period, and persistence of these symptoms was influenced both by genetic and shared environmental influences.…”
mentioning
confidence: 99%